Higher prevalence but later age at onset of asthma in cross-country skiers compared with general population - Mäki-Heikkilä, R.; Karjalainen, J.; Parkkari, J.; Huhtala, H.; Valtonen, M.; Lehtimäki, L. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Cross-country skiing causes strain in the airways because skiers train and compete in cold air. The aim of this survey was to investigate the prevalence and age at onset of asthma, asthma control, and use of asthma medication in Finnish competitive cross-country skiers. All cross-country skiers who were enrolled in the largest national competitions in winter 2019 (n = 1282) were invited to the study via the Finnish Ski Association. A control group (n = 1733) was matched for the responding skiers by age, gender, and region. The response rate was 27.4% (n = 351) for skiers and 19.5% (n = 338) for the controls. The prevalence of asthma was 25.9% in skiers and 9.2% in the controls (p < 0.001). Median (IQR) age at first asthma-related symptoms was higher in skiers than in the controls (13.0 (8.25-16.0) vs. 8.0 (2.25-11.75) years, p < 0.001), and the difference in asthma prevalence was evident only after the start of skiing career. Median (IQR) Asthma Control Test (ACT) score in skiers and controls with asthma was 22.0 (21-24) vs. 22.0 (19-24) (p = 0.611), and 89.0% of skiers and 77.4% of controls had well-controlled asthma (ACT score =20). In skiers with asthma, 82.4% used regular inhaled corticosteroids (ICS), and 80.2% used bronchodilators. A fixed combination of ICS +long-acting ß2-agonist was regularly used by 47.3% of the skiers and 22.6% of the controls with asthma (p = 0.016). In conclusion, asthma prevalence is about 2.5 times higher, and age at onset of asthma is later in skiers compared with the controls. Asthma in cross-country skiers is mostly well controlled and on regular maintenance treatment.